Catalytic Upgrading of Plastic Waste of Electric and Electronic Equipment (WEEE) Pyrolysis Vapors over Si–Al Ash Pellets in a Two-Stage Reactor - de Freitas Costa, Augusto; Ferreira, Caio; da Paz, Simone; Santos, Marcelo; Moreira, Luiz; Mendonça, Neyson; da Costa Assunção, Fernanda; de Freitas, Ana; Costa, Roseane; de Sousa Brandão, Isaque; da Costa, Carlos; da Mota, Sílvio; et al. (Energies (Basel), 2023)
This study investigated thermal cracking and catalytic upgrading of waste from electric and electronic equipment (WEEE) plastics on a semi-batch reactor coupled to a heated catalyst fixed bed (2-stage vapor cracking). The catalyst used is a Si–Al ash obtained from commercial activated carbon pellets treated with concentrated NaOH solution and calcination. The purpose of the study was to characterize the waste stream through its thermogravimetry analysis and pyrolysis products, study the effect of temperature (350–500 °C) and catalyst quantity (0.0–7.5 %.wt) on yields of reaction products, physical chemical properties, and chemical composition of bio-oil in order to understand and evaluate production of fuels and chemical feedstock by recycling of WEEE plastic through catalytic upgrading. Time-fractioned samples were taken in determined reaction times (15, 30, 45, and 60 min) to study the evolution of cracking reactions during experiment runs through changes to chemical composition (GC/MS). A comparison with other previous work is also presented to show similarities between different feedstocks using the same thermal unit. The results indicate composition of brominated acrylonitrile-butadiene-styrene (ABS), polycarbonate (PC), and high impact polystyrene (HIPS) for the WEEE plastic. The temperature of 350 °C produced better results when considering acid value but presented lower bio-oil yields (38%) and high gas yields (42%). Catalytic upgrading experiments revealed the increased presence of polycyclic aromatic hydrocarbons (PAH) with an increase in viscosity of bio-oil, increase in char yield (from 11% to 24%), and decrease in gas yields (15% to 5%). Chemical composition showed presence of aromatic hydrocarbons such as styrene, methyl-styrene, and diphenyl-propane and nitrogenated compounds such as benzene-butane-nitrile, phenolic compounds, PAHs, and brominated compounds. WEEE plastic pyrolysis is a challenging subject due to contaminant presence and varying composition, and chemical composition evaluation according to reaction time provides interesting insights into the evolution of semi-batch pyrolysis/catalytic upgrading experiments. Standardization and reproducibility of the tool should be conducted to continue the evaluation of pyrolysis and catalytic upgrading of a wide range of feedstocks.